Kelly's chance [large type] - Brunstetter, Wanda E. (Brunstetter, Wanda E. Brides of Lehigh Canal, 2010)
Life for Kelly McGregor is a daily drudge of driving her overbearing father's mules along Pennsylvania's Lehigh Canal. She dreams of one day owning an art gallery where her own drawings and paintings are on display. But these dreams don't include marriage . . . not after seeing what her father has done to her mother. How then can Mike Cooper, a general store owner, make her realize he is different than her father and wants to support her artistic talent? Will Kelly learn that dreams can walk hand in hand with a love created by God?